Effects of Polyphenols and Lignans of Phyllanthus amarus Schumach. and Thonn. on IL-1 and TNF- Secretions from LPS-induced THP-1-derived Macrophages - Mohd Azlan Nafiah (Tanjung Malim, 2024)
Effects of Polyphenols and Lignans of Phyllanthus amarus Schumach. and Thonn. on IL-1 and TNF- Secretions from LPS-induced THP-1-derived Macrophages by Mohd Azlan Nafiah